Mesin Ayak Dua Saluran Dilengkapi Pengarah untuk Produk Beras Jagung - Yohanes B Yokasing; Amiruddin Abdullah; Stanislaus Tamelab (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
A sieve machine is used to separate groups of granules based on size. Most separation sieves on two groups of sifted/filtered grains move immediately, but the unfiltered grains are removed by the operator turning the sieve sideways or lifting the unfiltered material. In addition, the sifted material is usually poured directly on the sieve wire. This slows the sifting process, and the buildup can damage the sieve. On the other hand, sieve materials, such as corn rice products, require two sizes of sieve wire holes. Design, make, and study the function, "The Sieve Machine's two-channel Equipped with Directions for Rice Corn". The specification of the sieve machine is as follows; it has two sifting channels, the sieve filter can be replaced, a swing arm drives the filter, the dynamo operates on 3/4 hp, rotation 1400 rpm, the capacity for one stage is ± 44.8 kg/hour, the capacity for corn rice ± 22 kg/hour (it's time to change the sieve). The study of engine performance on several variables showed that the smaller the lightening angle, the capacity increases; it is inversely proportional to the length of the spring and rotation. At angle 50 sieve capacity is 23.3 kg/hour, with the length of the spring being 90.5 mm, and on the size of the spring becoming 100.5 mm, the sieva capacity of 24.6 kg/hour. For angle 150, the capacity is reduced by 20.4 kg/hour. At rotation 230 rpm, 50 angles, decreased capacity, only 20.3 kg/hour, spring length 90.5 mm